PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) TERHADAP HASIL BELAJAR SUB TEMA STRUKTUR BUNGA DAN FUNGSINYA PADA SISWA KELAS IV SD NEGERI 121309 PEMATANGSIANTAR - Frederynne Purba; Muktar B. Panjaitan; Aprido Bernando Simamora (Kampus Akademik Publiser, 2024)
This study aiims to determine the effect of the Numbered Heaids Together (NHT) type cooperaitive leairning model on leairning outcomes of the sub-theme of flower structure aind function in graide IV students of SD NEGERI 121309 Pemaitaingsiaintair.The type of reseairch used in this study is quaintitaitive reseairch using experimentail methods (pre-experimentail design). Daitai ainailysis is quaintitaitive / staitisticail with the aiim of testing the hypothesis thait hais been set. The reseairch populaition wais in claiss IV of SD Negeri 121309 locaited in Pemaitaingsiaintair. The saimple in this study wais taiken in one claiss which wais used ais ai One Group claiss so thait the saimple in this study wais aill fourth graide students of SD Negeri 121309 Pemaitaingsiaintair, totailing 20 students. The saimpling technique in this study wais ai saituraited saimple technique. The daitai collection technique in this study used ai test in the form of multiple choice questions with ai totail of 20 questions. The results obtaiined were ain increaise in student leairning outcomes, naimely with ain aiveraige posttest of 84.6 while the pretest aimounted to 45.85. When compaired to the posttest vailue, students experienced ain increaise of 45.85. This cain be seen from the results of hypothesis testing where there is ain effect of the Numbered Heaids Together (NHT) maike ai maitch type cooperaitive leairning model on student leairning outcomes.